2020
DOI: 10.12697/akut.2019.25.06
|View full text |Cite
|
Sign up to set email alerts
|

The effect of motivational music on aerobic and anaerobic performance among overweight children

Abstract: The present study examined whether background music improves aerobic and anaerobic performance in overweight children. Eleven participants (14.6±1.5 yrs, BMI%: 94.3±6.5) performed aerobic (20m Shuttle Run) and anaerobic (repeated sprint test – RST) field tests. Ten participants (12.0±2.1 yrs, BMI%:97.4±1.6) performed aerobic (treadmill running) and anaerobic (Wingate Anaerobic Test – WAnT) laboratory tests. Treadmill running time was significantly longer with, compared to without, music (11.9±1.5 versus 10.6±2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…This increased pleasurable experience that music induces could be related to the higher levels of performance and perceived enjoyment associated to music in interval exercises [ 23 ]. This is partially in agreement with a recent study in adolescents, which showed that listening to motivational music was associated with a significant improvement of cardiorespiratory fitness in the treadmill run, but not in the SRT-original [ 46 ]. Accordingly, music could contribute to prolonged exercise durations at higher intensities [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…This increased pleasurable experience that music induces could be related to the higher levels of performance and perceived enjoyment associated to music in interval exercises [ 23 ]. This is partially in agreement with a recent study in adolescents, which showed that listening to motivational music was associated with a significant improvement of cardiorespiratory fitness in the treadmill run, but not in the SRT-original [ 46 ]. Accordingly, music could contribute to prolonged exercise durations at higher intensities [ 47 ].…”
Section: Discussionsupporting
confidence: 93%